Strategi Kepala Madrasah dalam Memperlancar Proses Pembelajaran Melalui Daring di MI Al-Muhajirin Denpasar pada Masa Pandemi Covid 19 Tahun Pelajaran 2019/2020 - Wahyu, Wahyu; Jumari, Jumari; Sudarsono, Sudarsono (STAI Denpasar Bali, 2022)
MI Al-Muhajirin is one of the schools in the Denpasar area that is implementing an online learning process. which underlies the author to conduct research. The purpose of this study was to find out 1) the Strategy of the Head of MI Al-Muhajirin during the Covid-19 Pandemic, 2) the Learning Process through Online at MI Al-Muhajirin Denpasar during the Covid-19 Pandemic Period, 3) The Strategy of the Head of Madrasah in Streamlining the Learning Process Online at MI Al-Muhajirin Denpasar during the Covid-19 Pandemic This type of research uses a descriptive qualitative approach. The data collection techniques used were interviews, observation, and documentation. Data analysis was carried out interactively, namely starting from data reduction, data presentation, and drawing conclusions. The results of the study reveal that: (1) The strategy of the madrasah principal has facilitated the basic needs of teachers such as preparing special quotas for teachers, preparing supporting media such as cameras, tripods, special rooms for making instructional videos. (2) The online learning process at MI Al-Muhajirin can be seen from the increase in student grades. (3) The strategy of the head of madrasah in an effort to facilitate online learning has been implemented, namely by preparing special cellphones and special classrooms.